2021
DOI: 10.1002/chem.202100816
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Selections of DNA‐Encoded Chemical Libraries on Carbonic Anhydrase IX‐Expressing Tumor Cells Reveal a Dependence on Ligand Valence

Abstract: DNA-encoded chemical libraries are typically screened against purified protein targets. Recently, cell-based selections with encoded chemical libraries have been described, commonly revealing suboptimal performance due to insufficient recovery of binding molecules. We used carbonic anhydrase IX (CAIX)-expressing tumor cells as a model system to optimize selection procedures with code-specific quantitative polymerase chain reaction (qPCR) as selection readout. Salt concentration and performing PCR on cell suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“… 88 , 89 Neri and co-workers also reported cell-based selections against CA-9, another membrane carbonic anhydrase isoform using dual-pharmacophore DELs. 90 CBS is a known ligand for CA-12 ( K d = 0.97 μM) 88 and can be used as a positive control in the selection. 88 , 89 We first tested whether the CBS-conjugated ssDNA, obtained from λ exo digestion, could selectively capture the CA-12 protein on live cells.…”
Section: Resultsmentioning
confidence: 99%
“… 88 , 89 Neri and co-workers also reported cell-based selections against CA-9, another membrane carbonic anhydrase isoform using dual-pharmacophore DELs. 90 CBS is a known ligand for CA-12 ( K d = 0.97 μM) 88 and can be used as a positive control in the selection. 88 , 89 We first tested whether the CBS-conjugated ssDNA, obtained from λ exo digestion, could selectively capture the CA-12 protein on live cells.…”
Section: Resultsmentioning
confidence: 99%
“…2a). 32,37,[97][98][99][100][101][102] The library is selected against immobilized targets, and the binding BBs can be decoded by sequencing the coding regions. Initially, the two BBs in a binding pair are separately decoded and their correlation is lost; thus, ESAC libraries were mostly used for affinity maturation of known ligands.…”
Section: Dual-pharmacophore Esac Librarymentioning
confidence: 99%
“…The authors did not estimate the target concentration, but the cell density was high (2 × 10 6 cells/50 μL); therefore, a high effective molarity of DOR is expected. Recently, Neri and co-workers comprehensively optimized the experimental parameters for cell-based DEL selections . Interestingly, they observed that bivalent ligands significantly improved the compound enrichment, suggesting that multivalency effect may be another way to drive the binding equilibrium on the cell surface.…”
Section: Selection With Complex Biological Targetsmentioning
confidence: 99%
“…Recently, Neri and co-workers comprehensively optimized the experimental parameters for cell-based DEL selections. 72 Interestingly, they observed that bivalent ligands significantly improved the compound enrichment, suggesting that multivalency effect may be another way to drive the binding equilibrium on the cell surface. However, this remains to be further examined with large-scale DEL selections and more targets.…”
Section: Membrane Proteinsmentioning
confidence: 99%